An investigation into citizens' trust in service delivery in Makhado Municipality, Limpopo Province, South Africa - Nefale, Mashangu Daphney (My University, 2019)
The purpose of the study was to investigate citizens’ level of trust in service delivery in Makhado Municipality by assessing the relationship between the performance of local government and the level of trust of citizens in the Municipality. In addition, the study sought to establish whether citizens’ involvement in decision-making in local government has an effect on their level of trust; and to establish the approaches which are important to improve citizens’ trust in local government. Data was collected through a questionnaire which was administered to 100 residents of Makhado Municipality. The findings of the study revealed that the citizens of Makhado Municipality do not trust in the service delivery in the Municipality. Residents are dissatisfied with most of the services they are receiving from the Municipality. It was determined that water shortage is the biggest problem in the Municipality, and residents spend days without water which poses serious risks to their health. Housing provision is another area that residents are displeased with. There is no transparency in the allocation of RDP houses, nepotism and corruption are rife and the quality of these houses is also poor. The area of roads and storm water supply is also of concern. Roads and streets in the municipality are in a bad state with potholes everywhere. Some roads and streets that were tarred have been turned into gravel roads, gravel roads in villages are also in a bad state of disrepair because they are not consistently maintained. The findings further revealed that service delivery challenges in the Municipality are caused by a lack of consultation and leadership, as well as corruption and if these three factors are addressed, service delivery will improve and trust would be fostered amongst citizens. This study recommends that the Municipality should develop its own anti-corruption strategies; invest in research and form partnerships with tertiary institutions; improve public participation and consultation; and collaborate with other government departments. Unfortunately, the research findings cannot be generalised to other municipalities since they differ in terms of categories and responsibilities. Nonetheless, some ideologies of the recommendations can be applied to other municipalities.
Thesis (MPAM.) -- University of Limpopo, 2019
Keywords: Service delivery; Trust; Government; Basic services; Poor performance; Corruption; Integrated development plan and Acts.; Municipal government -- South Africa -- Limpopo; Local government -- South Africa -- Limpopo; Municipal services -- South Africa -- Limpopo